Self-education and information technologies – changeability of forms and difficulty of classification - Sergo KURULISZWILI (Edukacja Ustawiczna Dorosłych)
Information technologies determine changes in learning processes and have a significant impact on the revision of self-education methods. The evolution of this form of learning requires reflection and research. The article addresses three issues that are important in this context: an attempt to organise the phenomenon in its new version; location of the newly defined form of incidental e-learning as a self-learning process in the context of heutagogy and microlearning, and finally, some answers to doubts concerning the role of social media in formal learning. The first two issues are based on the results of previous research and literature studies, as well as author's personal observations. To explain the last issue, author presents the results of his research in the extent and nature of the use of social media as a tool to support teaching and learning process at primary, junior high/high school and higher education level. The main research problem undertaken by the author is the attempt to answer the question whether new media are properly used as means of self-education supporting general development of a student.